Postmenopausal ovarian hyperandrogenism of surgically treated patients: a case report and scoping review with individual patient’s data analysis - Forte, Angelo; D’Elia, Lanfranco; De Luca, Carmine; Fiore, Antonella; Barbato, Antonio; Abate, Veronica; Vergatti, Anita; Verde, Nunzia; De Filippo, Gianpaolo; Venetucci, Pietro; De Angelis, Maria Chiara; Di Crescenzo, Rosa Maria; et al. (Frontiers in Endocrinology, 2025)
IntroductionPostmenopausal hyperandrogenism (PH) is a rare clinical condition caused by relative or absolute androgen excess after menopause. Tumorous or non-tumorous ovarian diseases can cause PH.MethodsIn this two-section hybrid study, the first section describes the case of a patient with PH caused by an ovarian disease and surgically treated. The second section shows the results of a scoping review with individual patient data (IPD) analysis, which was performed to define the biochemical and clinical features of PH patients with tumorous or non-tumorous ovarian diseases surgically treated. All PH cases caused by anything but ovarian disease and/or without surgical indication and/or without histological diagnosis were excluded.ResultsDue to imaging suspicion, our PH patient underwent robotic hysterectomy with bilateral ovariectomy. A Leydig cell tumor stage 1A was diagnosed. At 6 months after surgery, the PH was resolved. Overall, the IPD analysis included 280 PH patients with ovarian diseases (oPH) surgically treated. Among them, histological examination showed 174 tumorous oPH and 106 non-tumorous oPH. Patients with tumorous oPH showed lower body mass index and lower levels of luteinizing hormone (LH) and follicle-stimulating hormone (FSH), as well as higher levels of testosterone, dehydroepiandrosterone sulfate (DHEA-S), 17-OH progesterone, and estradiol compared with non-tumorous oPH patients. We defined the levels of testosterone (≥9.8 nmol/L), LH (≤15 mUI/ml), FSH (≤35 mUI/ml), and DHEA-S (≥1.6 μmol/L) able to differentiate between tumorous and non-tumorous oPH patients with suitable sensitivity (≥68.6%) and specificity (≥72.7%). No PH recurrence was described after surgery.DiscussionThe study results provide useful biochemical parameters to support the diagnosis of ovarian tumor in patients with oPH.